The Impact of Motivation on the Academic Performance of University Students - Dokhykh, Raihanah Ali (Journal of Humanities & Social Sciences, 2021)
This study evaluates how motivation influences the academic performances of university students. The sample includes 400 higher education students attending different universities in Saudi Arabia. The questionnaire was the data gathering method that was chosen by the researcher to complete this study. The study reveals that both intrinsic and extrinsic motivations positively impact the academic performance of students. Academic performance increased by a percentage increase of between 23% and 34 %. Overall, the model showed a significant jump (p<0,05). The researcher found that the individual elements associated with extrinsic motivation – rejection of alternative options: increase by 17%; career and qualifications: increase by 9%; social enjoyment: increase by 7%; social pressure: increase by 4%. The researcher also found that both intrinsic and extrinsic motivations are critical elements in the academic success of students and student’s performances that tend to consistently fluctuate between good and average/poor. Their performance seems to be guided by the presence of an external reward. Further studies are needed to determine if intrinsically motivated students can be further motivated.